A rechargeable non-aqueous Mg-Br2 battery. (October 2016) - Yao, Xiahui; Luo, Jingru; Dong, Qi; Wang, Dunwei
Abstract: Owing to its low cost and high volumetric capacity, Mg is a promising anode material for energy storage applications. Previous research has identified the cathode chemistry as a major challenge that must be addressed for further development of Mg-based batteries. In response to this challenge, here we show Br2 -based conversion chemistry is a potential route toward rechargeable Mg-batteries. Compared with Mg-ion or Mg-air chemistries, the Mg-Br2 system features fast kinetics and good cyclability. To solve the issues of poor electrolyte stability, a non-aqueous, dual-electrolyte scheme was employed for this proof-of-concept demonstration. The anolyte consisted of Mg(TFSI)2 dissolved in a monoglyme and diglyme mixture. The catholyte was composed of Mg(TFSI)2 in PYR14 TFSI ionic liquid mixed with active bromine species. When Mg was used as the anode, an open circuit voltage of 3.0 V (vs. Mg 2+ /Mg) was measured. The prototypical cell was successfully discharged and charged for over 20 cycles with consistently high coulombic efficiencies (ca. 96%). Graphical abstract: Highlights: A dual-electrolyte design is proposed and demonstrated for Mg-Br2 Battery applications. Good stability for both the Mg anode and Br2 cathode is obtained. High Columbic efficiencies (96%) are measured. Up to 20 cycles of repeated discharge and recharge are achieved.